Having an Anthropocene Body: Hydrocarbons, Biofuels and Metabolism. (March 2014) - Mackenzie, Adrian
What does it mean to have an Anthropocene body? The Anthropocene period is putatively defined by flows of hydrocarbons and hydrocarbon derivatives (fuels, plastics, fertilizers, etc.), and the very term 'Anthropocene' suggests an increasing awareness of the finitude and contingency of contemporary corporealities. This article explores the idea of modelling an Anthropocene body as a living/non-living metabolic process. While identifying bodies with molecules raises a host of problems, metabolism and hydrocarbon biomolecules display a gamut of forms of possession and ways of having a body. Conversion between living and non-living forms of possession can be traced in contemporary genomic science and particularly in synthetic biology as they engineer microbes to produce next-generation biofuels. In contrast to fossil fuels, these fuels derive from genomically re-engineered microbes that digest biomass or photosynthesize to produce hydrocarbons. The problematic contemporary production of these fuels might help us to articulate what it means to have a body as a metabolic manifold of living and non-living forms of possession.